Aspekty kosztowe i przychodowe kontraktów w zakładach opieki zdrowotnej - Pauka, Marek; Prędkiewicz, Paweł (Cost and Revenue Aspects of Contracts in Health Care Centres, 2008)
n the paper, the authors discuss the problems that accompany calculating the rentability of contracts in health care centres. The main issue is a relatively huge level of fixed cost, dichotomous character of participants in the market (private aimed to gain profit and public). The traditional way of private business controlling has to be modified.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 47-53